Kolaborasi Komponen Pendidikan Dalam Mewujudkan Pembelajaran Bermakna Pada Siswa Kelas II Sekolah Dasar - Trivena Meiliana Koroh; Widiastuti Widiastuti (Universitas Negeri Makassar, 2021)
This research aims to describe the form of collaboration application between educational components in realizing learning in grade II elementary school students. The research method used is a qualitative descriptive research method with a phenomenological approach to question natural phenomena. The subjects of this study were 92 people, consisting of 31 students of class II-B, 1 teacher of class II-B, 1 parallel teacher of class II-A, 1 representative of the school in the curriculum field, and 31 parents of students. The primary data of this research are based on the results of direct observations, while the secondary data are from documents related to collaboration, such as lesson plans, teacher research results, and the author's reflections on observations. The research instrument using observation and documentation techniques in the data. The results showed that to improve the quality of students positively and with quality, it is necessary to manage education through good collaboration from the school, family, and community so that positive stimulus through the interaction of educational components can develop aspects of students holistically. This study concludes that there are three forms of collaboration for educational components that can be carried out in realizing classroom learning, namely teacher and student collaboration, teacher collaboration, parallel teachers, and vice principal in curriculum, and teacher and parent collaboration (PaL's).